I've got my eyes on you [compact disc, unabridged] : a novel - Clark, Mary Higgins (Audioworks/Simon & Schuster Audio, 2018)
After a party when her parents are away, eighteen-year-old Kerry Dowling is found fully dressed at the bottom of the family pool. Kerry's older sister Aline, a twenty-eight-year-old guidance counsellor, is determined to assist the Prosecutor's Office in learning the truth. She does not realize that now she is putting her own life in danger.